2006
DOI: 10.1098/rspb.2006.3505
|View full text |Cite
|
Sign up to set email alerts
|

Demographic structure and pathogen dynamics on the network of livestock movements in Great Britain

Abstract: Using a novel interpretation of dynamic networks, we analyse the network of livestock movements in Great Britain in order to determine the risk of a large epidemic of foot-and-mouth disease (FMD). This network is exceptionally well characterized, as there are legal requirements that the date, source, destination and number of animals be recorded and held on central databases. We identify a percolation threshold in the structure of the livestock network, indicating that, while there is little possibility of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
232
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(237 citation statements)
references
References 26 publications
(43 reference statements)
1
232
0
Order By: Relevance
“…Markets may play key roles in the spread of infectious diseases in livestock movement networks (KAO et al, 2006). For instance, Robinson and Christley (2007) found that auction markets played an important role in foot-and-mouth disease outbreaks in Great Britain.…”
Section: Discussionmentioning
confidence: 99%
“…Markets may play key roles in the spread of infectious diseases in livestock movement networks (KAO et al, 2006). For instance, Robinson and Christley (2007) found that auction markets played an important role in foot-and-mouth disease outbreaks in Great Britain.…”
Section: Discussionmentioning
confidence: 99%
“…From the Cattle Tracing System (18) we have individual records of the movement of cattle between the 150,000 farms, markets, and slaughterhouses in Great Britain (SI Text). Both of these movement datasets can be conceptualized as relatively sparse networks; the analysis of such networks yields a wide range of important information on the pattern of movements and the structure of the populations (19,20). Here, however, we are interested in how such movements lead to the percolation of infection through the population, and we show that great care is needed if realistic rates of spread are to be predicted.…”
mentioning
confidence: 99%
“…This rate can either be the same for all edges (19,21) or can be proportional to the strength of the The authors declare no conflict of interest.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While networks have been used to reveal the importance of heterogeneity in social contacts (VanderWaal & Ezenwa, 2016;White et al, 2017) and in spatial networks of animal movements (Kao et al, 2006;Keeling et al, 2010;Jacoby & Freeman, 2016), there has been little empirical research quantifying variation in indirect transmission opportunities. This is important as quantifying and characterising this variation might facilitate the targeting of management efforts at key sources of environmental transmission.…”
Section: Discussionmentioning
confidence: 99%